Production process of wood waste fiber-based automobile interior trim panel
By combining the landscaping ground cover plant residues with forest waste fibers, hot grinding and sizing, adding specific resin and zinc oxide, and going through vulcanization pre-pressing and maturation hot pressing processes, the problem of forest waste fibers and waste fibers in the existing technology is solved. The problem of difficult to effectively utilize the residues of landscaping ground cover plants has enabled the production of high-performance automotive interior panels and reduced formaldehyde emissions.
Patent Information
- Application Number
- CN202411609174.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-12
Smart Images

Figure CN119347912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiberboard processing, in particular to a production process of a forest waste fiber-based automobile interior trim panel. Background Art
[0002] my country has abundant forest fiber resources that can be used as raw materials for bioethanol. The "three wastes" in the forestry industry alone (logging waste, timber making waste, and processing waste) amount to 133 million tons per year, most of which are discarded or incinerated. If half of them are converted into bioethanol, they can replace 21% of gasoline consumption. In addition, my country's fast-growing artificial forest resources also have high development potential. At present, in my country, the annual output of garden green plant residues produced by natural withering or artificial pruning during the growth process, including common branches, branches and twigs produced after pruning trees and shrubs, is about 20 million to 40 million tons, and the problem of its treatment and disposal is becoming increasingly prominent. Those skilled in the art are in urgent need of developing a production process for automotive interior panels based on forest waste fibers to meet existing usage needs and performance requirements. Summary of the invention
[0003] In view of the above problems, the present invention aims to provide a production process of forest waste fiber-based automobile interior trim panels.
[0004] The present invention is achieved through the following technical solutions: A production process for automobile interior panels based on forest waste fiber, comprising the steps of chipping, screening to obtain wood chips of predetermined size, drying, sorting, paving after gluing, and cooling, sanding, sawing and stacking after cutting, characterized in that it also includes the following steps: (1) preparing residual fiber emulsion slurry from garden greening ground cover plants by crushing and pulping; (2) hot grinding and waxing process (this process is carried out after the screening step): executing hot grinding process parameters, spraying the fiber emulsion slurry obtained in the previous step into the grinding chamber of the hot grinder through a metering pump, and obtaining forest waste fiber from wood chips of predetermined size through hot grinding of the hot grinder, and the forest waste fiber and residual fiber are mixed together. After the emulsion slurry is evenly mixed, it is sprayed out to obtain mixed wood fibers; and when the total hot grinding time reaches 50% to 60%, the heated and melted paraffin in which 40% to 50% by mass of tert-butylphenol formaldehyde resin is dissolved and dispersed is directly sprayed into the grinding chamber of the hot grinding machine through a metering pump, and hot grinding is continued until the total hot grinding time is reached; (3) Gluing: Then, urea-formaldehyde resin glue containing 1% to 2% by mass of zinc oxide is applied to the obtained mixed wood fibers in the spraying pipe of the hot grinding machine, and then enters the drying process; (4) After paving to form a slab, it is then subjected to vulcanization pre-pressing, aging and hot pressing before cutting; the above process is carried out after the paving step. After cutting, cooling, sanding, sawing and stacking are carried out.
[0005] Furthermore, in the gluing process of step (3), the amount of urea-formaldehyde resin adhesive applied is controlled within a ratio range of 8% to 10% by weight of absolute dry urea-formaldehyde resin adhesive to absolute dry mixed wood fibers.
[0006] Furthermore, the predetermined size of the wood chips in step (2) is 20-30 mm×10-20 mm×5-10 mm.
[0007] Furthermore, the absolute dry forest waste fibers of the mixed wood fibers obtained in step (3) account for 70% to 80% of the absolute dry mixed wood fibers.
[0008] Gardening ground cover plants refer to low plants that can cover the ground and are used in gardening, including herbs and woody plants, dwarf bushes, prostrate or semi-climbing shrubs and vines. Because of their small overall size, their fiber slurry can be obtained by simply crushing and beating.
[0009] In daily production practice and quality inspection, it was unexpectedly discovered that the fiberboard products from a certain batch had high surface bonding strength, low formaldehyde emission, high internal bonding strength, and low water absorption thickness expansion rate. The comprehensive performance was better than that of conventional fiberboard products produced in daily production. The performance fluctuated and received good feedback and evaluation from downstream customers. However, this performance improvement phenomenon was not stable, and it did not reappear in subsequent production. Therefore, a comprehensive investigation was carried out from the aspects of production process, employee operation process parameters, equipment, etc. It was found that the main reason for the improvement in performance was when additional batches of landscaping ground cover plant residues (waste materials) were accidentally introduced into the wood raw materials. These landscaping ground cover plant residues come from branches, branches and twigs produced after pruning trees and shrubs, etc., and when they are waste materials of euonymus, goose down vine, and dandelion roots, the improvement phenomenon is particularly prominent. When observing its production phenomenon, these residues have sticky fibers and a gray milky white appearance during processing, and have a certain bonding effect.
[0010] Furthermore, the garden greening ground cover plant residues are one or more of the residues of hyacinthus annuus, hyacinthus velvet and dandelion. Hyacinthus annuus is an evergreen plant belonging to the shrub plant. Hyacinthus annuus, hyacinthus velvet and dandelion are more common in Anhui and have strong adaptability to the environment. After garden greening and reprocessing, a large number of stems and roots are eliminated and are mainly abandoned in wasteland or used as fuel.
[0011] Furthermore, the process parameters of the hot mill in step (2) are set as discharge temperature of 60-65°C, hot mill pressure of 7.2-8 bar, preheating bin temperature of 80-90°C, cooking pressure of 7.5-8 bar, cooking time of 130-160s, cooking temperature of 140-145°C, preheating bin material level of 75%-80%, plugging screw speed of 47-50rpm, discharging screw speed of 65-75rpm, discharge valve opening of 50%-70%, pressure difference of 0.2-0.3MPa, and total hot mill time of 3-5min.
[0012] The difference between the grinding chamber pressure and the cooking cylinder pressure is the pressure difference.
[0013] Furthermore, the paraffin in step (2) is 58# fully refined paraffin, and the addition amount is 0.5% to 0.6% of the absolute dry mixed wood fiber.
[0014] Furthermore, the vulcanization pre-pressing in step (4) is as follows: pre-pressing pressure 1.5-1.8 MPa, vulcanization pre-pressing temperature 160-170°C, pre-pressing time 25-30 s / mm, and the aging hot pressing process is as follows: high pressure 1.6-2.2 MPa, heat transfer section pressure 0.3-0.6 MPa, thickness setting pressure 0.8-1.0 MPa, hot pressing temperature 200-220°C, and hot pressing time 25-30 s / mm.
[0015] Furthermore, the solid content of the residual fiber latex slurry in step (4) is 50% to 60%.
[0016] Furthermore, the moisture content of the slab formed by paving in step (4) is 8% to 9%.
[0017] Beneficial effects of the present invention: The forest waste fiber-based automobile interior decoration board disclosed in the present invention is prepared by crushing and beating the residual plant residues of garden greening ground cover into residual fiber emulsion slurry, executing the hot grinding process parameters, and spraying the fiber emulsion slurry obtained in the previous step into the grinding chamber of the hot grinding machine through a metering pump. The forest waste fiber and the residual fiber emulsion slurry are uniformly mixed, and the paraffin wax with para-tert-butylphenol formaldehyde resin dissolved and dispersed after heating and melting is further mixed. The urea-formaldehyde resin glue contains 1% to 2% by mass of zinc oxide. Compared with conventional fiberboards, some of the raw materials use lower cost The residues of gardening ground cover plants, zinc oxide and tert-butylphenol formaldehyde resin contain latex components in the latex slurry, which has a certain bonding effect. The cross-linking of latex is achieved through the vulcanizing agent tert-butylphenol formaldehyde resin and the activating agent zinc oxide, as well as the subsequent vulcanization pre-pressing and aging hot pressing, which not only improves the strength of the fiberboard, but also reduces the use of urea-formaldehyde resin glue and the release of formaldehyde. At the same time, tert-butylphenol formaldehyde resin can be evenly dissolved in paraffin, and no additional processing equipment is required. Technical improvements can be achieved on the existing production line. The residues of gardening ground cover plants such as Euonymus provide both wood fiber and latex components in the production process, achieving efficient conversion and high-value utilization. They not only provide the base material of fiberboard as wood fiber, but also improve the strength of fiberboard as a bonding component. Zinc oxide can improve the vulcanization of latex components and enhance the bonding effect of fiberboard. After testing, it was found that the fiberboard has high static bending strength, high internal bonding strength, high surface bonding strength, low water absorption thickness expansion rate, low formaldehyde emission, and a wide range of raw material sources with low cost. It can also absorb waste fibers from landscaping and forestry, and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a process flow chart of the production process of forest waste fiber-based automobile interior panels; Figure 2 This is a photo of the forest waste fiber-based automobile interior trim panel obtained in Example 1. DETAILED DESCRIPTION
[0019] The present invention is described below with specific examples, but is not intended to be limiting of the present invention. Example 1
[0020] Raw materials and equipment: Raw materials: flap cooler X268, cooling plate conveyor X269, cooling plate conveyor X267; two-sand frame sander BSG2613VGD, four-sand frame sander BSG2713VGD, four-sand frame sander BSG2713VXXD, drum chipper BX2110, hot grinder Andritz48; Gaoqiao Petrochemical 58# fully refined paraffin; the residue of landscaping ground cover plants is the residue of processed dandelion roots of Yuguan Ziyu in Neixiang, Nanyang (about 90 yuan / t); the abandoned hard miscellaneous wood branches purchased from Gaotai Township, Funan have a moisture content of 35%, no decay and deterioration, no sand, mud, ice and snow and other foreign matter on the surface (wrapping the raw materials), no diseased, rotten, insect-infested and other diseased wood, the small head diameter shall not be less than 4cm, the large head diameter shall not be greater than 16cm, and the average wood length is 100cm. Jiaxiang Jiatai Chemical's JTHG010 urea-formaldehyde resin glue meets the GB / T 14732-2017 standard, with a free formaldehyde content of less than 0.1% and a solid content of 50% milky white liquid; Fuyang Hongli Chemical's Type I zinc oxide; Fuyang Hangmo P9402 tert-butylphenol formaldehyde resin.
[0021] The processed dandelion root residues are crushed and pulped to prepare residue fiber emulsion slurry; the solid content of the residue fiber emulsion slurry is 50%, the average length of the residue fibers is 1 mm, and the aspect ratio is 40.
[0022] A production process for automobile interior trim panels based on forest waste fibers comprises the steps of chipping, screening to obtain wood chips of predetermined size, hot grinding, waxing, gluing, drying after gluing, sorting, paving, cooling after cutting, sanding, edge sawing and stacking.
[0023] The predetermined size of the wood chips is 20mm×10mm×5mm; the amount of urea-formaldehyde resin adhesive applied is controlled within the ratio of 8% by weight of the absolute dry urea-formaldehyde resin adhesive to the absolute dry mixed wood fiber; the hot grinding and waxing process (performed after the screening step): execute the hot grinding process parameters, the hot grinding process parameters of the hot mill are set to the pulping temperature of 60°C, the hot mill pressure of 7.2bar, the preheating bin temperature of 8°C, the cooking pressure of 7.5bar, the cooking time of 130s, the cooking temperature of 140, the preheating bin level of 75%, the plugging screw speed of 47rpm, the discharging screw speed of 65rpm, the discharge valve opening of 50%, and the pressure difference of 0.2MPa; the fiber emulsion slurry obtained in the previous step is sprayed into the grinding chamber of the hot mill by a metering pump, and the wood chips of the predetermined size are obtained by hot grinding of the hot mill to obtain forest waste fibers, and the forest waste fibers and the residual fiber emulsion slurry are evenly mixed and discharged through spraying to obtain mixed wood fibers ; The mixed wood fiber is made of 70% of the mass of the absolute dry mixed wood fiber; and when the total hot grinding time reaches 50%, the heated and melted paraffin in which 40% by mass of tert-butylphenol formaldehyde resin is dissolved and dispersed is directly sprayed into the grinding chamber of the hot grinder through a metering pump, and the hot grinding is continued until the total hot grinding time is reached. The amount of paraffin added is 0.5% of the absolute dry mixed wood fiber; sizing: Then the mixed wood fiber obtained is sizing in the spray pipe of the hot grinder. Apply urea-formaldehyde resin glue containing 1% by mass of zinc oxide, and enter the drying process; after paving to form a slab, it is subjected to vulcanization pre-pressing, aging and hot pressing before cutting. The vulcanization pre-pressing process is: pre-pressing pressure 1.5MPa, vulcanization pre-pressing temperature 160℃, pre-pressing time 25s / mm, and the aging and hot pressing process is: high pressure 1.6MPa, heat transfer section pressure 0.3MPa, thickness setting pressure 0.8MPa, hot pressing temperature 200℃, and hot pressing time 25s / mm.
[0024] Specifically, Figure 1 As shown, the entire process of forest waste fiber-based automotive interior panels includes the following four major sections.
[0025] 1. Material preparation section: It includes two parts: chipping and screening: Chipping: In order to ensure the specifications and quality of the wood chips after processing, the moisture content of the raw material branches is 35%. For branches with lower moisture content, the branches are humidified to 35% before chipping. The wood is transported from the raw material yard to the raw material platform by a loader, and then sent to the chipper by the loader for processing (wood chip specifications: length × width × height: 20mm × 10mm × 5mm), and the chipped wood chips are sent to the wood chip bin by a belt conveyor for storage. Screening: The wood chips in the wood chip bin are quantitatively discharged by a spiral and sent to the wood chip screening machine by a belt conveyor for screening. The unqualified large pieces of wood screened out are returned to the chipper for processing; the too fine bark and debris are sent to the waste shed as fuel for the heating energy center.
[0026] 2. Fiber preparation section: The fiber preparation section mainly includes three parts: hot grinding, sizing and drying, and sorting. Hot grinding: The prepared wood chip raw materials are transported to the main workshop through a closed conveying pipeline. The wood chips enter the wood chip preheating bin through a belt conveyor. The preheated wood chips are continuously and evenly fed into the vertical steam generator for steaming and softening treatment through a vibrating discharger and a cork screw feeder. The steam generator is equipped with a new type of γ-ray level meter to control the wood chip level and cooking time. The softened wood chips are sent to the grinding chamber of the hot mill through a feeder and a screw conveyor for fiber separation. At the same time, the heated and melted paraffin with 40% by mass of tert-butylphenol formaldehyde resin dissolved and dispersed is directly sprayed into the grinding chamber of the hot mill through a metering pump. The paraffin can evenly adhere to the fiber surface and effectively lubricate the grinding disc. The ground fiber is sent to the fiber drying system by a continuous spiral discharge valve.
[0027] Gluing and drying: The glued fiber discharged from the hot mill has a high moisture content and cannot be transported by air flow and evenly laid. The fiber must be dried. The fiber must be dried to a moisture content of 8% to meet the requirements of subsequent processes such as air flow transportation, laying molding, and hot pressing. The hot-milled fiber is sent to the dryer by the fiber spray pipe, and the prepared urea-formaldehyde resin glue is sent to the hot mill spray pipe by a metering pump. The material is mixed while the material moves. The wind speed in the wind tube is 24m / s. After 6 seconds, the moisture content of the material is reduced to 8% (the glue mixing process is all carried out in a closed pipeline). The heating medium of the dryer is the high-temperature flue gas from the thermal energy center and the mixed gas of the air supply fan. The high-temperature flue gas (temperature 340℃) from the thermal energy center is dedusted by a multi-tube dust collector, mixed with air in a mixing chamber, and then enters the drying pipeline to directly contact the material. The hot air flow is used for flash drying during pipeline transportation. At the end of the drying pipeline, the fiber and the moist air are separated by a cyclone separator, and the fiber is dried to the moisture content required by the process. The drying cyclone outlet is 65℃, and the dried fibers enter the fiber sorting machine for sorting. The drying system is equipped with a moisture content meter, spark detection, fire extinguishing and temperature control devices, and the entire system is automatically controlled by the PLC system. Sorting: The dried fibers enter the fiber sorting machine. Under the action of the sorting machine, qualified fibers enter the fiber bin on the top of the paving machine through the secondary air delivery system for storage, and unqualified fiber clusters are removed by gravity and sent to the energy center for fuel combustion.
[0028] 3. Sheet metal forming section: The slab forming process mainly includes two sections: paving, pre-pressing and hot pressing; Paving and pre-pressing: A rotary feeder is installed at the bottom of the dry fiber silo. The fibers sent out by the feeder continuously enter the storage bin of the BP3313 paving machine, and then the fiber wood is sent to the discharge port through the conveyor belt at the bottom of the bin. The material is forced to be thrown by the throwing roller, providing a uniform and continuous material flow to the paving head. Under the action of a group of inclined throwing rollers at the paving head, the material flow falls evenly on the conveyor belt before paving, so that the fiber forms a slab, which is sent to the pre-pressing machine by the forming belt. After pre-pressing and forming, it is tested by a metal detector and then sent to the continuous flat press for hot pressing; unqualified slabs are scattered by the slab recovery device and sent to the fiber bin of the paving machine by a set of pneumatic conveying devices for recycling. Hot pressing: The qualified pre-pressed slabs are sent to the feed port of the continuous flat press by the retractable conveyor belt and enter the press under the clamping of the upper and lower steel belts.
[0029] 4. The post-processing section of the board mainly includes five parts: board slitting, cooling, sanding, edge sawing and inspection: Board slitting: After the continuous rough board comes out of the hot press, the board is tested by the thickness measurement and weighing system. The qualified boards are cut into boards of certain specifications by the horizontal cutting saw SJ21D and enter the next process. Cooling: The qualified boards are cooled in the flip cooler. After natural cooling and stacking, they are sent to the intermediate warehouse for storage by the automatic stacking system.
[0030] Sanding: After being stacked for 2 days, the rough boards are sent to the sanding line by the automatic stacking system for sanding. This project plans to adopt a 2+4+4 ten-sand rack combination configuration process. The boards meet the thickness requirements after coarse sanding, medium sanding and fine sanding. Edge sawing: After the boards are sanded, SC15 edge sawing treatment is performed to make them meet the product size requirements. Inspection and grading: The finished boards after sanding enter the inspection and grading section. The unqualified waste boards are sent to the thermal energy center as fuel. The qualified boards are sent to the finished product warehouse by forklift after being graded and stacked. The product specifications are 2440mm×1220mm×1mm.
[0031] Product performance: density 0.94g / cm 3 ; Moisture content 4.7%; Density deviation within the board -2.0%, +1.4; Static bending strength 50.4MPa; Elastic modulus 4843MPa; Internal bonding strength 1.69MPa, surface bonding strength 2.36MPa, water absorption thickness expansion rate 22.0%, formaldehyde release 4.9mg / 100g.
[0032] Comparative Example 1 Compared with Example 1, this comparative example omits the residual fiber emulsion slurry, p-tert-butylphenol formaldehyde resin, and zinc oxide during the hot grinding process, that is, the paraffin does not contain P9402 resin, the urea-formaldehyde resin glue does not contain zinc oxide, and the fiberboard is a conventional fiberboard made of pure forest waste hardwood branches.
[0033] Product performance: density 0.94g / cm 3 ; Moisture content 4.6%; Density deviation within the board -2.1%, +1.5; Static bending strength 48.3MPa; Elastic modulus 4641MPa; Internal bonding strength 1.54MPa, surface bonding strength 2.30MPa, water absorption thickness expansion rate 24.0%, formaldehyde release 12.9mg / 100g. Example 2
[0034] The equipment is the same as that in Example 1. The raw material of landscaping ground cover plant residue is a mixture of 1:1 mass ratio of euonymus residue and goose down vine residue (100 yuan / t). Gaoqiao Petrochemical 58# fully refined paraffin wax; purchased from the abandoned hardwood branches and twigs of Gaotai Township, Funan, with a moisture content of 40%, no decay and deterioration, no sand, mud, ice and snow on the surface (wrapping the raw materials), no diseased wood, insect pests, etc., the small head diameter shall not be less than 4cm, the large head diameter shall not be greater than 16cm, and the average length of the wood is 100cm. Jiaxiang Jiatai Chemical's JTHG010 urea-formaldehyde resin glue meets the GB / T 14732-2017 standard, with a free formaldehyde content of <0.1% and a solid content of 50% milky white liquid; containing Shanjinhua Type I zinc oxide; Fuyang Hangmo P9401 tert-butylphenol formaldehyde resin.
[0035] The residues of garden greening ground cover plants in a ratio of 1:1, namely, the residues of Melilotus officinalis of Funan Kaiyuan Green Company and the residues of Green Goose Down Rattan of Funan Linsen Garden, were crushed and pulped to prepare residue fiber emulsion slurry; the solid content of the residue fiber emulsion slurry was 60%.
[0036] A production process for automobile interior trim panels based on forest waste fibers comprises the steps of chipping, screening to obtain wood chips of predetermined size, hot grinding, waxing, gluing, drying after gluing, sorting, paving, cooling after cutting, sanding, edge sawing and stacking.
[0037] The predetermined size of the wood chips is 30mm×20mm×10mm; the amount of urea-formaldehyde resin adhesive applied is controlled within the ratio range of 10% by weight of the absolute dry urea-formaldehyde resin adhesive to the absolute dry mixed wood fiber; wherein the hot grinding and waxing process (performed after the screening step): execute the hot grinding process parameters, the hot grinding process parameters of the hot mill are set to the pulping temperature of 65°C, the hot mill pressure of 8bar, the preheating bin temperature of 90°C, the cooking pressure of 8bar, the cooking time of 160s, the cooking temperature of 145°C, the preheating bin level of 80%, the plug screw speed of 50rpm, the discharge screw speed of 75rpm, the discharge valve opening of 70%, the pressure difference of 0.3MPa, and the total hot grinding time of 5min; the fiber emulsion slurry obtained in the previous step is sprayed into the grinding chamber of the hot mill by a metering pump, and the wood chips of the predetermined size are obtained by hot grinding of the hot mill to obtain forest waste fibers, and the forest waste fibers and the residual fiber emulsion slurry are evenly mixed and sprayed out to obtain mixed wood fibers; the mixed wood fibers The absolute dry forest waste fiber accounts for 80% of the absolute dry mixed wood fiber mass; and when the total hot grinding time reaches 60%, the heated and melted paraffin in which 50% by mass of tert-butylphenol formaldehyde resin is dissolved and dispersed is directly sprayed into the grinding chamber of the hot grinder through a metering pump, and the hot grinding is continued until the total hot grinding time is reached. The amount of paraffin added is 0.6% of the absolute dry mixed wood fiber; sizing: Then, in the spray pipe of the hot grinder, the obtained mixed wood fiber is sizing containing 2% by mass of oxidizing agent. Zinc urea-formaldehyde resin glue enters the drying process; after paving to form a slab, it is subjected to vulcanization pre-pressing, aging hot pressing and then cutting. The vulcanization pre-pressing process is: pre-pressing pressure 1.8MPa, vulcanization pre-pressing temperature 170℃, pre-pressing time 30s / mm, and the aging hot pressing process is: high pressure 2.2MPa, heat transfer section pressure 0.6MPa, thickness setting pressure 1.0MPa, hot pressing temperature 220℃, hot pressing time 30s / mm. The product specifications are 2440mm×1220mm×1mm.
[0038] Product performance: density 0.94g / cm 3 ; Moisture content 4.8%; Density deviation within the board -2.0%, +1.4; Static bending strength 50.7MPa; Elastic modulus 4898MPa; Internal bonding strength 1.77MPa, surface bonding strength 2.45MPa, water absorption thickness expansion rate 21.3%, formaldehyde release 4.8mg / 100g.
[0039] Note: The moisture content is determined according to the moisture content determination method specified in 4.3 of GB / T17657-2013. The static bending strength and elastic modulus are determined according to the static bending strength and elastic modulus determination methods specified in 4.7 of GB / T17657-2013, and the specimen is balanced. If the specimen is not damaged, the maximum load is taken as Fmax for static bending strength calculation. The internal bonding strength is determined according to the internal bonding (bonding) strength determination method specified in 4.11 of GB / T17657-2013, and the specimen is balanced. The surface bonding strength is determined according to the test method specified in 6.9 of GB / T11718-2021, and the specimen is balanced. The water absorption thickness expansion rate is determined according to the water absorption expansion rate determination method 1 specified in 4.4 of GB / T17657-2013, and the immersion time is required to be 24h, and the measurement after immersion is completed within 10min. The water absorption rate is determined according to the 24h water absorption rate determination method specified in 4.6 of GB / T17657-2013. The formaldehyde emission is determined according to the formaldehyde emission determination regulations in GB18580-2017.
Claims
1. A production process for automobile interior panels based on forest waste fiber, comprising the steps of chipping, screening to obtain wood chips of predetermined size, drying, sorting, paving after gluing, and cooling, sanding, sawing and stacking after cutting, characterized in that: The following steps are also included: (1) crushing and beating the residual landscaping plants to prepare residual fiber emulsion slurry; (2) hot grinding and waxing process: executing the hot grinding process parameters, spraying the fiber emulsion slurry obtained in the previous step into the grinding chamber of the hot grinding machine through a metering pump, and hot grinding wood chips of a predetermined size to obtain forest waste fiber by the hot grinding machine, and the forest waste fiber and the residual fiber emulsion slurry are uniformly mixed and sprayed out to obtain mixed wood fiber; and when the total hot grinding time reaches 50% to 60%, The heated and melted paraffin in which 40% to 50% by mass of tert-butylphenol formaldehyde resin is dissolved and dispersed is directly sprayed into the grinding chamber of the hot mill through a metering pump, and hot grinding is continued until the total hot grinding time is reached; (3) Gluing: Then, urea-formaldehyde resin glue containing 1% to 2% by mass of zinc oxide is applied to the obtained mixed wood fibers in the spray pipe of the hot mill, and then enters the drying process; (4) After paving to form a slab, it is subjected to vulcanization pre-pressing, aging hot pressing, and then slitting.
2. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: In the gluing process of step (3), the amount of urea-formaldehyde resin adhesive applied is controlled within a ratio range of 8% to 10% by weight of absolute dry urea-formaldehyde resin adhesive to absolute dry mixed wood fibers.
3. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The predetermined size of the wood chips in step (2) is 20-30 mm×10-20 mm×5-10 mm.
4. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The mixed wood fiber obtained in step (3) contains 70% to 80% of the mass of the mixed wood fiber.
5. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The garden greening ground cover plant residues are one or more of the residues of Euonymus japonicus, residues of Eupatorium foetida, and residues of Taraxacum officinale.
6. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The process parameters of the hot mill in step (2) are as follows: the discharge temperature is 60-65°C, the hot mill pressure is 7.2-8 bar, the preheating bin temperature is 80-90°C, the cooking pressure is 7.5-8 bar, the cooking time is 130-160s, the cooking temperature is 140-145°C, the preheating bin level is 75%-80%, the plugging screw speed is 47-50rpm, the discharging screw speed is 65-75rpm, the discharge valve opening is 50%-70%, the pressure difference is 0.2-0.3MPa, and the total hot mill time is 3-5min.
7. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The paraffin wax in step (2) is 58# fully refined paraffin wax, and the addition amount is 0.5% to 0.6% of the absolute dry mixed wood fiber.
8. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The vulcanization pre-pressing in step (4) is as follows: pre-pressing pressure 1.5-1.8 MPa, vulcanization pre-pressing temperature 160-170°C, pre-pressing time 25-30 s / mm, and the aging hot pressing process is as follows: high pressure 1.6-2.2 MPa, heat transfer section pressure 0.3-0.6 MPa, thickness setting pressure 0.8-1.0 MPa, hot pressing temperature 200-220°C, and hot pressing time 25-30 s / mm.
9. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The solid content of the residual fiber latex slurry in step (4) is 50% to 60%.
10. The production process of a forest waste fiber-based automobile interior trim panel according to claim 1, characterized in that: The moisture content of the slab formed by paving in step (4) is 8% to 9%.
Citation Information
Patent Citations
Waste wood framework composite fiber board and manufacturing method thereof
CN108724419A
Heat-vulcanized water-soluble adhesive of unvulcanized rubber and vulcanized rubber and preparation method of heat-vulcanized water-soluble adhesive
CN112126376A
Method and apparatus for manufacturing a wood fibreboard
EP2939807A1